Kontemplasi Desain Kurikulum PAI Futuristik Predisposisi Partikularitas Anak dan Interes Publik : Studi Multikasus - Harun Arrosyid; Mulyadi; Endah K. Purwaningtyas (TADRIS: Jurnal Pendidikan Islam, 2021)
This article attempts to analyze and find (1) the futuristic paradigm of Islamic religious education curriculum design (2) implementation of Islamic religious education curriculum design in character strengthening (3) the implications of Islamic religious education curriculum design on strengthening the character of students. This research implements a qualitative approach with a case study research type with a multi-case design model. The research was carried out at SD Plus Muhammadiyah Brawijaya, Mojokerto City and MI Ismailiyah New Paradigm, Mojokerto City. Data collection techniques apply in-depth interviews, observation of roles and documentation. Data analysis used multi-case analysis which was carried out in two stages, namely analysis of individual case data (individual case) and cross-case data analysis (cross case analysis). Checking data using credibility and confirmability. The results showed that: (1) Islamic religious education curriculum design based on the dynamics of life (adaptability centered design) was formulated as a response to the phenomenon of the transformation of the times and public interest (2) implementation of Islamic religious education curriculum design through textual and contextual learning models with a humanist approach. -religious and humanist-sufistic provide positive excesses in strengthening the character of students (3) the implications of Islamic religious education curriculum design on character strengthening are the formation of self-pity (behavioral attitude) with the intention of creating individuals who seek to get closer to Allah swt (taqarrub ilallah).